Model Awal Berbasis System Dynamics Untuk Pengelolaan Sampah Rumah Tangga Di Suatu Kota - Vinsensius Widdy Tri Prasetyo; Petrus Setya Murdapa; Chatarina Dian Indrawati; Theresia Liris Windyaningrum (Jompa Research and Development, 2024)
Household waste management has become a serious challenge for many cities amid population growth and urbanization. Poorly managed waste has the potential to pollute the environment, burden landfills, and decrease the quality of life for communities. This challenge is exacerbated by the low level of waste sorting at the source and illegal dumping. This research develops a system dynamics-based model in the form of a Stock and Flow Diagram (SFD) to analyze the flow of household waste from source to final processing, encompassing community behavior, infrastructure, and intervention policies. The study evaluates two approaches: subsidies for waste processing facilities and strengthening law enforcement against illegal waste disposal. Although the results indicate that law enforcement is more effective in reducing illegal waste, neither approach has succeeded in significantly decreasing the amount of household waste. This shows that existing policies are insufficient to change community behavior. Therefore, a holistic and sustainable approach is needed, including community education, improved accessibility to facilities, and more effective law enforcement to reduce the impact of household waste.